Comparing estimated and measured glomerular filtration rate in children with posterior urethral valve - Manish Ora; Lokeshwaran Madurai Kalimuthu; Prabhakar Mishra; Aftab Hasan Nazar; Dharmendra S Bhadauria; Sukanta Barai; Sanjay Gambhir (Wolters Kluwer Medknow Publications, 2023)
Background: Posterior urethral valve (PUV) is obstructive uropathy that may lead to chronic kidney disease (CKD) and end-stage renal disease (ESRD) in children. Glomerular filtration rate (GFR) measurement remains the gold standard for renal function measurement. However, due to its less availability and cumbersome, it is not commonly used, and GFR is estimated utilizing various endogenous filtration markers. Objective: This study includes pediatric patients with PUV. We aimed to compare the measured GFR (mGFR) with various creatinine-based estimated GFR methods (eGFR). Materials and Methods: A single-center retrospective study included 62 treated cases of PUV, postvalve fulguration. The mGFR measured by 99mTc-diethylenetriaminepentaacetate in vitro method and compared with eight eGFR (Schwartz, Cockcroft-Gault [CG], Counahan-Barratt [CB], CKD Epidemiology Collaboration [CKD-EPI], full-age spectrum [FAS] age, FAS height (FAS Ht), Schwartz-Lyon [SL], and Ht independent). Patients were subdivided into different CKD grades and compared with various eGFR. Discussion: PUV is a common cause of CKD in children and needs special consideration as there is growth retardation associated with it. It decreases creatinine production and thus fallacies in eGFR measurement. There is a requisite to identify and closely monitor the subset of patients with baseline decreased renal function and therefore at risk of developing ESRD. Results: A total of 62 patients were included. Mean age and serum creatinine levels were 8.02 ± 5.53 years and 1.15 ± 0.95 mg/dl (range: 0.4-4.5), respectively. The mean mGFR was 61.6 ± 31.80 mL/min/1.73 m2 and a positive variable correlation was 0.46-0.77 between mGFR and eGFR. Based on mGFR, there were 14 (22.6%), 21 (33.8%), 13 (20.9%), 9 (14.5%), and 5 (8.1%) patients in Grades I-V, respectively. The correct classification of the CKD grades was noted in 25 (40.3%), 16 (25.8%), 32 (51.6%), 16 (25.8%), 25 (40.3%), 27 (43.5%), 26 (41.9%), and 28 (45.2%) patients by Schwartz, CG, CB, CKD-EPI, FAS age, FAS Ht, SL, and Ht-independent equation. The eGFR overestimates GFR at the lower level and underestimates at higher levels. Conclusion: Our results confirm the considerable limitations of various creatinine-based clearance methods for estimating actual GFR. The creatinine clearance-based eGFR should not replace the measurement of the GFR. An initial measure of the mGFR followed by serial follow-up with the eGFR equation may be done. The most accurate eGFR equations are CB for Grade II, SL or Ht independent for Grade III, FAS age for Grade IV, and SL for Grade V CKD.